Status, constraints and future prospects of Murrah buffaloes in India - KUMAR, MANOJ; DAHIYA, S P; RATWAN, POONAM; KUMAR, SUNIL; CHITRA, ANIL (The Indian Journal of Animal Sciences, 2020)
In the present review, an attempt has been made to explore Murrah buffalo, an important milch breed for its performance, genetic parameters, constraints and future scenario. In India, price of milk is decided on basis of fat percentage and buffalo milk fetches more money compared to cow milk to dairy farmers. Production and reproduction performances are among most important considerations to determine the profitability of any dairy farm. The production, reproduction and functional traits of Murrah buffaloes as reported by different workers at different organized farm were reviewed. Literature revealed that the 305-days lactation milk yield, 305-days lactation fat yield, 305-days lactation SNF yield, 305-days lactation total solid yield, peak yield, Fat %, SNF %, lactation length, dry period, age at first calving, service period, conception rate, pregnancy rate and calving interval varied from 1365±03 to 2086.17±44.66 kg, 118.3 to 167.38±4.46 kg,185.5±3.4 to 198.88±5.05 kg, 336.2±6.1 to 360.61±9.25 kg, 9.96 to 11.13±0.44 kg, 6.84% to 8.17%, 9.36% to 9.76%, 267.15 to 321.62 days,121.68 to 250.5 days, 1202 to 1618.83 days, 135.79 to 308 days, 68.80%, and 428.30 to 559.6 days, respectively in Murrah buffaloes. Heritability and repeatability estimates for the production, 38% reproduction and functional traits of Murrah buffaloes were also reviewed. Breeding, feeding, health and housing management practices have much impact on production and reproduction performance of animals and ultimately influence the economy of dairy farmers. Constraints in all these aspects are the obstacles to implement better animal husbandry practices in dairy animals and these should be overcome by taking suitable measures.